Molecular biomarkers and genetic determinants of non-alcoholic fatty liver disease / Tan Hwa Li - Tan, Hwa Li (2019)
Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease encompassing non-alcoholic fatty liver (NAFL) and non-alcoholic steatohepatitis (NASH). NAFL is relatively benign but NASH has a higher rate of progression to develop into liver cirrhosis and hepatocellular carcinoma. Stratification of NASH from NAFL is important for disease monitoring and medical interventions. Genetic variations such as single nucleotide polymorphisms (SNPs) and copy number variations (CNVs) contribute to the phenotypic variation and rate of disease progression. MicroRNAs (miRNAs) are small non-coding, stably expressed RNAs in the biofluids that regulate gene expression post-transcriptionally affecting disease phenotype. This study aimed to investigate the potential genetic variants and biomarkers involved in the development of NAFLD with focus to NASH. A total of 232 healthy controls and 249 biopsy-proven NAFLD patients were recruited. Quantitative polymerase chain reaction (qPCR) was used to genotype the SNPs on the glucokinase regulatory gene (GCKR) (rs1260326 and rs780094) and CNV 13q12.11. Sequence-specific primer (SSP) technique was applied for HLA typing. Differential expression of miRNAs was screened and validated in the healthy controls, NAFL and NASH patients. The diagnostic values of miRNAs were assessed using area under receiver operating characteristic (AUROC) curves. Both GCKR rs1260326 and rs780094 were associated with susceptibility to NASH (OR 1.55, 95 % CI 1.10–2.17, P = 0.013; and OR 1.56, 95 % CI 1.10–2.20, P = 0.012, respectively) and NASH with significant fibrosis (fibrosis score ≥ 2) (OR 1.50, 95 % CI 1.01–2.21, P = 0.044; and OR 1.52, 95 % CI 1.03–2.26, P = 0.038, respectively). Histological data showed a significant association of GCKR rs1260326 with higher iv steatosis grade (OR 1.76, 95 % CI 1.08–2.85, P = 0.04). The CNV gain in the 13q12.11 was significantly associated with a greater risk of NAFLD (OR 2.22, 95% CI 1.42–3.46, P = 0.0004) and NASH (OR 2.33, 95% CI 1.47–3.68, P = 0.0003). HLA-DQB1*06 allele group was significantly associated with reduced risk of NASH with advanced fibrosis compared to NASH without advanced fibrosis (OR 0.272, 95% CI 0.14-0.55, P < 0.001). The DQB1*06 allele group was also significantly associated with lower risk of lobular inflammation (OR 0.84, 95% CI 0.39-0.97, P = 0.016) and a lower risk of hepatic fibrosis in NAFLD patients (OR 0.30, 95% CI 0.14-0.67, P< 0.001 suggesting its protective value in conferring a milder form of the disease. Increased expression of miR-122, miR-193, miR-192, miR-34a and miR-125b were demonstrated in NASH (P <0.001, P = 0.001, P = 0.015, P = 0.021 and P = 0.042, respectively). The miR-122 has the best diagnostic accuracy for NASH (AUROC = 0.73) and combination of miR-122 and AST gave the best prediction for NASH from NAFL (AUROC = 0.785). The miR-122, miR-193band miR-125b were significantly upregulated in significant fibrosis (P < 0.0001, P = 0.001 and P = 0.003, respectively) with miR-122 having the highest AUROC of 0.736. This study showed the potential of SNPs and CNVs in predicting the risk of NASH and the role of miRNAs as molecular biomarkers of NASH. Keywords: NAFLD, NASH, genetic variations, microRNA, interaction of HLA